2019
DOI: 10.1002/cam4.2661
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor‐associated pituitary‐adrenal dysfunction: A systematic review and meta‐analysis

Abstract: With the growing use of immune checkpoint inhibitors (ICIs), case reports of rare yet life‐threatening pituitary‐adrenal dysfunctions, particularly for hypopituitarism, are increasingly being published. In this analysis, we focus on these events by including the most recent publications and reports from early phase I/II and phase III clinical trials and comparing the incidence and risks across different ICI regimens. PubMed, Embase, and the Cochrane Library were systematically searched from inception to April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 146 publications
(172 reference statements)
1
27
1
2
Order By: Relevance
“…Several authors have reported high IH frequencies (11–13%) ( 15 , 16 ) and relative risk for all-grade IH as high as 22.03 ( 17 ). However, according to the latest reviews and meta-analyses IH incidences are lower but they notably depend on the type of ICI used and the treatment regimen ( 1 , 18 , 19 , 20 , 21 , 22 , 23 ). Combination therapy has been associated with the highest estimated incidence of IH, ranging from 7.7 to 10.5%, remarkably higher than monotherapy with anti-CTLA-4 (1.8–5.6%) or anti-PD-1 drugs (0.3–1.1%) ( 1 , 18 , 19 , 20 , 21 , 22 , 23 ).…”
Section: Immune Checkpoint Inhibitor-induced Hypophysitismentioning
confidence: 99%
“…Several authors have reported high IH frequencies (11–13%) ( 15 , 16 ) and relative risk for all-grade IH as high as 22.03 ( 17 ). However, according to the latest reviews and meta-analyses IH incidences are lower but they notably depend on the type of ICI used and the treatment regimen ( 1 , 18 , 19 , 20 , 21 , 22 , 23 ). Combination therapy has been associated with the highest estimated incidence of IH, ranging from 7.7 to 10.5%, remarkably higher than monotherapy with anti-CTLA-4 (1.8–5.6%) or anti-PD-1 drugs (0.3–1.1%) ( 1 , 18 , 19 , 20 , 21 , 22 , 23 ).…”
Section: Immune Checkpoint Inhibitor-induced Hypophysitismentioning
confidence: 99%
“…In this study, among the three types of ICIs, only patients treated with CTLA‐4 inhibitors were at higher risk of primary adrenal insufficiency. The reason might be that the PD‐1/PD‐L1 axis activated restricted subsets of T cells in the tumor microenvironment and circulation 44 . However, the CTLA‐4 immune checkpoint participated in the early phase of the immune response during T‐cell priming and activation and enhanced the immunosuppressive activity of Treg cells, thus having a broad impact on the immune system 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The reason might be that the PD-1/PD-L1 axis activated restricted subsets of T cells in the tumor microenvironment and circulation. 44 However, the CTLA-4 immune checkpoint participated in the early phase of the immune response during T-cell priming and activation and enhanced the immunosuppressive activity of Treg cells, thus having a broad impact on the immune system. 45 Therefore, plasma cortisol rhythm and blood electrolyte levels should be monitored in patients with tumors treated with ICIs, especially CTLA-4 inhibitors.…”
Section: Different Types Of Icis and Endocrine Adverse Eventsmentioning
confidence: 99%
“…Pituitary dysfunction and adrenal insufficiency have also been well documented irAEs of ICI therapy. In a meta-analysis conducted by Lu et al [ 28 ], the incidence of adrenal insufficiency was found to be 2.43% (95%CI: 1.73%-3.22%), while the rate of hypophysitis was reported to be 3.25% (95%CI: 2.15%-4.51%). Hypophysitis most frequently occurs secondary to CTLA-4 inhibitor therapy[ 28 ].…”
Section: Endocrinementioning
confidence: 99%
“…In a meta-analysis conducted by Lu et al [ 28 ], the incidence of adrenal insufficiency was found to be 2.43% (95%CI: 1.73%-3.22%), while the rate of hypophysitis was reported to be 3.25% (95%CI: 2.15%-4.51%). Hypophysitis most frequently occurs secondary to CTLA-4 inhibitor therapy[ 28 ]. The specific mechanism is not well understood; however, multiple theories are currently being investigated.…”
Section: Endocrinementioning
confidence: 99%